2019
DOI: 10.3390/agriculture9050093
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and Skin Injuries of Piglets Originating from a Novel Group Farrowing System Before and After Weaning

Abstract: The aim of this study was to analyse a novel group farrowing system (GH) concerning piglets’ behaviour, skin injuries and body weight gain, to test its animal friendliness. Skin injuries and weight gain were compared to piglets originating from conventional individual housing (IH) before and after weaning. The GH system had five farrowing pens without crates, a common area and an area only available for piglets. In total, 34 litters were studied. Four days after the GH-piglets had left the pens during lactatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(95 reference statements)
1
11
0
Order By: Relevance
“…Beyer and Wechsler [20] assessed the influence of the type of floor on the claw condition of weaners and found that even a difference of 1 mm in the slat gap had an impact on forming and severity of claw lesions (wall bruising and coroner lesions). Moreover, injuries and skin lesions in piglets often result from the hierarchical fights among piglets as a result of mixing unfamiliar piglets at weaning [21]. Leg weakness often causes stress and pain to the pig, and also impairs the piglet´s ability to compete at the feeding through.…”
Section: Discussionmentioning
confidence: 99%
“…Beyer and Wechsler [20] assessed the influence of the type of floor on the claw condition of weaners and found that even a difference of 1 mm in the slat gap had an impact on forming and severity of claw lesions (wall bruising and coroner lesions). Moreover, injuries and skin lesions in piglets often result from the hierarchical fights among piglets as a result of mixing unfamiliar piglets at weaning [21]. Leg weakness often causes stress and pain to the pig, and also impairs the piglet´s ability to compete at the feeding through.…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, alternative systems without crates are becoming increasingly important in today's pig production, aimed to enhance both the sow's and piglets' welfare. [2][3][4][5][6][7] In these loose housing systems, the sows can either be single housed or group housed together with other sows and their litters. In group housing systems, piglets meet unknown conspecifics (sows and piglets from other litters) before weaning, and this early socialisation can reduce aggressive behaviour and skin injuries when piglets are mixed after weaning.…”
Section: Introductionmentioning
confidence: 99%
“…In group housing systems, piglets meet unknown conspecifics (sows and piglets from other litters) before weaning, and this early socialisation can reduce aggressive behaviour and skin injuries when piglets are mixed after weaning. [5][6][7] Early socialisation corresponds to the speciesspecific behaviour of pigs. It is known for wild boars that the sow returns to her group together with her offspring four to 12 days after farrowing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that weaning impacts the structure, morphology, and functioning of the intestines, the immune response of piglets, feed intake, growth rate, morbidity, and mortality indexes [201]. Weaning is a gradual process that would end at approximately 17 weeks of age in the wild [202]. The way weaning is handled varies among production systems [50].…”
Section: Weaning Agementioning
confidence: 99%